2009
DOI: 10.1177/1758834009337664
|View full text |Cite
|
Sign up to set email alerts
|

Review: Therapeutic opportunities in noncutaneous melanoma

Abstract: Recent evidence suggests that the biology of noncutaneous melanoma differs significantly from cutaneous melanoma and may provide therapeutic opportunity. The most frequent sites of origin of noncutaneous melanoma are the eye and mucosal surfaces. Although noncutaneous melanomas are an uncommon group of cancers (representing less than 10% of all melanomas) a greater understanding of their genetic and molecular abnormalites is being translated into novel treatment strategies. These developments are important bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…1,2 Mucosal melanomas account for approximately only 1.3% of all melanoma cases. 3,4 While the incidence of cutaneous melanomas has steadily increased over the last 20 years (153.5 cases per million per year), mucosal melanoma incidences have remained stable (2.2 cases per million per year). 1 Mucosal melanomas also tend to occur in an older patient population than cutaneous ones, with a mean age of 67 years.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1,2 Mucosal melanomas account for approximately only 1.3% of all melanoma cases. 3,4 While the incidence of cutaneous melanomas has steadily increased over the last 20 years (153.5 cases per million per year), mucosal melanoma incidences have remained stable (2.2 cases per million per year). 1 Mucosal melanomas also tend to occur in an older patient population than cutaneous ones, with a mean age of 67 years.…”
Section: Discussionmentioning
confidence: 97%
“…1 Mucosal melanomas also tend to occur in an older patient population than cutaneous ones, with a mean age of 67 years. 4,5 It is well known that chronic sun exposure and sun damage are the primary risk factor for cutaneous melanomas; however, similar risk factors have not been discovered for mucosal melanomas, and these lesions lack a clear association with ultraviolet exposure. 1,5,6 They exhibit higher rates among women compared with men, mainly due to higher numbers of genital tract melanomas, which accounted for more than 56% of these lesions in women.…”
mentioning
confidence: 97%
“…Therefore, mutation(s) in alternate reading frame protein dysregulate p53 function and play a role in tumor immune evasion. It has been observed that c 4 (CDK4) gene amplification, is an independent oncogene, and is more common in acral and mucosal melanoma than the CSID and NCSID cutaneous melanomas [20,47]. It has been observed that mutations or deletions of PTEN are concurrent with mutations in BRAF but not in N-RAS [20].…”
Section: Molecular Pathwaysmentioning
confidence: 99%
“…Approximately 90% of melanomas are cutaneous, but they can also occur at any anatomic location-for example, eye, mucosa, head and neck surfaces, and along the gastrointestinal and genitourinary tracts 2,5,6 . Cutaneous malignant melanoma (cmm) is responsible for the largest proportion (60% -80%) of skin cancer-related deaths 4,[7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%